1999
DOI: 10.1002/(sici)1097-4636(1999)48:6<913::aid-jbm22>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell technology and bioceramics: From cell to gene engineering

Abstract: Mesenchymal stem cells reside in bone marrow and, when these cells are incorporated into porous ceramics, the composites exhibit osteo-chondrogenic phenotypic expression in ectopic (subcutaneous and intramuscular) or orthotopic sites. The expressional cascade is dependent upon the material properties of the delivery vehicle. Bioactive ceramics provide a suitable substrate for the attachment of the cells. This is followed by osteogenic differentiation directly on the surface of the ceramic, which results in bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
333
1
6

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 553 publications
(347 citation statements)
references
References 94 publications
7
333
1
6
Order By: Relevance
“…[2][3][4] Kuboki et al 25 reported that the pore size of HA controlled phenotype expression in BMP-induced osteogenesis or chondrogenesis, and the commitment to osteogenic lineage occurred by increasing the pore size of porous HA ceramics. Although the mechanism that determines whether the MSCs differentiate into osteoblasts or chondroblasts is unclear, it appears that the differentiation of MSCs is strongly affected by the surrounding microenvironment such as oxygen tension, properties of biomaterials, cell densities, and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Kuboki et al 25 reported that the pore size of HA controlled phenotype expression in BMP-induced osteogenesis or chondrogenesis, and the commitment to osteogenic lineage occurred by increasing the pore size of porous HA ceramics. Although the mechanism that determines whether the MSCs differentiate into osteoblasts or chondroblasts is unclear, it appears that the differentiation of MSCs is strongly affected by the surrounding microenvironment such as oxygen tension, properties of biomaterials, cell densities, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2 We already established an experimental model to show consistent bone formation in the pores of hydroxyapatite (HA) ceramic combined with the culture-expanded bone marrow mesenchymal stem cells (MSCs) from rat or human bone marrow. [2][3][4] The porous HA ceramic exhibits a biocompatible and osteoconductive nature and is therefore an excellent material for supporting the osteogenic differentiation of MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…This has been recapitulated by different articles, particularly in the field concerning bone marrow-derived stem cells [3][4][5]. As one of every 100,000 nucleated cells derived from bone marrow is a stem cell, a procedure of isolation is required to decrease the volume of material injected [6].…”
Section: Introductionmentioning
confidence: 99%
“…5 These cells have been identified in several tissues such as bone marrow, 6 adipose tissue, 7 synovial tissue 8 and dental papilla tissue. 9 MSCs are thought to be an effective tool for regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%